SOFT POWER KEPALA SEKOLAH: Kecerdasan Emosional dalam Menyelesaikan Konflik Internal Sekolah - Yunita Kristanti; Nur Efendi; Abd. Aziz (Yayasan Sukma, 2025)
This study discusses the role of soft power of school principals through emotional intelligence in resolving internal school conflicts. This issue is important to examine because interpersonal conflicts in schools often disrupt the work and learning climate, while authoritarian approaches are no longer relevant in the era of humanistic leadership. The purpose of this study is to describe the forms of emotional strategies of school principals and identify the supporting and inhibiting factors of soft power effectiveness. This study employs a qualitative approach using case study methodology, with data collection techniques including participatory observation, in-depth interviews, and documentation, analyzed through the interactive model of Miles and Huberman. The results indicate that the primary strategies employed by school principals include empathy, dialogic communication, moral exemplary behavior, collective participation, and emotional recognition. Supporting factors include integrity, experience, collective support, and an inclusive organizational culture, while barriers include rigid bureaucracy, lack of emotional training, and low self-reflection. The conclusion of this study indicates that soft power based on emotional intelligence is an effective and strategic approach in building harmony and resolving conflicts in the school environment. These findings contribute to enriching transformative and humanistic leadership practices in the field of education.